1994
DOI: 10.1152/jappl.1994.76.1.204
|View full text |Cite
|
Sign up to set email alerts
|

Very large range of baroreflex sympathetic control of vascular resistance in human skeletal muscle and skin

Abstract: We analyzed in the forearm of "comfortably warm" male volunteers 1) reflex sympathetic vascular resistance changes evoked by short-term graded [1.5-min exposure to 15, 40, 55, and 70 mmHg and high and barely tolerated (77-95 mmHg)] lower body negative pressure (LBNP) and 2) resistance changes evoked by abolition of control sympathetic vasoconstrictor tone (anesthetic axillary nerve block). Graded LBNP caused graded neurogenic vasoconstriction with pronounced average flow decline at high LBNP from 3.7 to 0.8 ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…These investigators demonstrated that sympathetically mediated changes in leg blood flow or leg vascular resistance reached a plateau before the sympathoexcitation stimulus had reached its maximum, primarily due to elevated sympathetic nerve activity. Indeed, the vascular response to a given change in sympathetic nerve activity was lower when the prestimulus sympathetic nerve activity was high compared with that under a condition of low sympathetic nerve activity (22). Thus it is plausible that during the large increases in MSNA induced by PEMI, the sympathetically mediated changes in leg vascular conductance were reduced compared with rest, thereby contributing to the decrease in the gain of the ABR peripheral arc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These investigators demonstrated that sympathetically mediated changes in leg blood flow or leg vascular resistance reached a plateau before the sympathoexcitation stimulus had reached its maximum, primarily due to elevated sympathetic nerve activity. Indeed, the vascular response to a given change in sympathetic nerve activity was lower when the prestimulus sympathetic nerve activity was high compared with that under a condition of low sympathetic nerve activity (22). Thus it is plausible that during the large increases in MSNA induced by PEMI, the sympathetically mediated changes in leg vascular conductance were reduced compared with rest, thereby contributing to the decrease in the gain of the ABR peripheral arc.…”
Section: Discussionmentioning
confidence: 99%
“…Recent animal investigations have demonstrated that transfer function analyses for the closed-loop identification of these baroreflex arcs can estimate the open-loop baroreflex characteristics (14,17). Thus the operating gain of the neural arc can be evaluated from the transfer function gain of the relationship between arterial BP and efferent sympathetic nerve activity (i.e., MSNA), whereas the peripheral arc gain can be evaluated from the transfer function gain of the relationship between efferent sympathetic nerve activity and the nerve-effector junction, which for the control of BP is primarily the transduction of MSNA to a change in vascular smooth muscle tone [i.e., vascular conductance (22,39)]. However, to date, no studies have attempted to identify the interactions between the neural and peripheral baroreflex arcs in humans and how these may be modified by exercise.…”
mentioning
confidence: 99%
“…Peripheral vascular responses to changes in muscle sympathetic nerve activity (MSNA) are critical for the effective regulation of arterial blood pressure (Fadel, 2008; Kiviniemi et al 2011). Numerous studies have demonstrated that the human forearm vasculature significantly constricts in response to robust elevations in reflex‐mediated MSNA (Lundvall & Edfeldt, 1994; Davy et al 1998; Minson et al 2000; Ray & Monahan, 2002). However, to our knowledge, no information is available describing the influence of spontaneously occurring MSNA on forearm vasoconstrictor responses.…”
Section: Introductionmentioning
confidence: 99%
“…Splanchnic vasoconstriction accounts for one third of the increased vascular resistance during normal levels of orthostatic stress. Skin and muscle vasoconstriction accounts for approximately 40% of the increased vascular resistance during normal levels of orthostatic stress that is simulated by a lower negative body pressure of-40 mm Hg [4,5] and for an even greater percentage of the total during higher levels of this simulated orthostatic stress [6,7]. We define the term "vasoconstrictor reserve" as the amount of additional vasoconstriction that can ultimately be made available during orthostatic stress.…”
mentioning
confidence: 99%